Color superconductivity in an external magnetic field - Gorbar, E. V. (American Physical Society (APS), 2000)
We study color superconductivity in an external magnetic field. We discuss the reason why the mixing angles in color-flavor locked (CFL) and two-flavor superconductivity (2SC) phases are different despite the fact that the CFL gap goes to the 2SC gap for ms→∞. Although flavor symmetry is explicitly broken in an external magnetic field, we show that all values of the gaps in their coset spaces of possible solutions in the CFL phase are equivalent in an external magnetic field. ©2000 The American Physical Society.